Position-based QoS multicast routing protocol for mobile Ad Hoc Networks - Khalifa, Othman Omran; Hassan Abdalla Hashim, Aisha; Qabajeh, Mohammad M.; Qabajeh, Liana K. (2010)
Recently, the necessity of applications where many users have to interact in a close manner over mobile Ad-Hoc networks gains high popularity. Multicast communication is essential in this type of applications to reduce the overhead of group communication. For group-oriented multimedia applications Quality of Service (QoS) provision is a basic requirement, which makes an efficient QoS multicast routing protocol a very important issue. This paper proposes a locationbased QoS multicast routing protocol via cooperation between Network and MAC layers. Along with this protocol, a location and group membership management scheme has been proposed. Unlike some of multicast routing protocols, the proposed approach limits maintaining the network topology to certain nodes to reduce control overhead and reduce bandwidth consumption. Our proposed protocol is scalable for large area networks with large multicast members regardless of the network density. Also, it achieves a significant reduction in processing overhead compared to flat QoS algorithms.